2007
DOI: 10.1189/jlb.0106046
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent resistance to allergen-induced lung pathophysiology in mice correlates with rate of apoptosis of lung-derived eosinophils

Abstract: Although exposed to similar allergic and environmental stimuli, not all humans develop asthma. Similarly, mouse strains vary in the degree of pathophysiology seen following induction of experimental asthma. Three mouse strains (CBA/Ca, BALB/c, and C57BL/6) were used to determine if the extent and duration of inflammation influenced the degree of lung tissue damage in an OVA-induced allergic asthma model. Airways obstruction, leukocyte infiltration, edema, eosinophil accumulation, and degranulation were less se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 62 publications
4
30
0
Order By: Relevance
“…The increase in bacterial load could also be explained by the reduction in serum TNF-␣ concentration and the inability of the MLNs to produce this particular cytokine, as this cytokine is known to play an important role in the confinement of mycobacteria (46). Interstrain variations have been described for mice with regard to inflammatory and immunological functions (19,47). Macrophages from different mouse strains also exhibit different sensitivities to the glucocorticoid dexamethasone (19).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in bacterial load could also be explained by the reduction in serum TNF-␣ concentration and the inability of the MLNs to produce this particular cytokine, as this cytokine is known to play an important role in the confinement of mycobacteria (46). Interstrain variations have been described for mice with regard to inflammatory and immunological functions (19,47). Macrophages from different mouse strains also exhibit different sensitivities to the glucocorticoid dexamethasone (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, strain-dependent resistance in the asthma model in mice has been reported to correlate with the apoptosis rate of lung-derived eosinophils [50]. Another possibility might be the difference in the degree of eosinophil activation.…”
Section: Untangling the Role Of Eosinophils In Experimental Trichinelmentioning
confidence: 99%
“…Recent studies found that making the aluminum adjuvant into nanometer form could induce the specific antibody in mice quickly and at a high level, and that compared with other forms of aluminum adjuvant, it could induce humoral immunity earlier (Frey et al, 1999). After consulting the relevant literature, we found the amount of OVA used in animal models generally ranges from 10 to 100 μg (Yamaki et al, 2005;Tumes et al, 2007;Liu et al, 2010;Oh et al, 2011), whereas the amount of Al(OH) 3 ranges from 1 and 5 mg. Moreover, there are several forms of Al(OH) 3 used in these experiments including powder, gel, solution, and other dosage forms (Yamaki et al, 2005;Zhao et al, 2005;Su et al, 2006;Tumes et al, 2007;Mo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…After consulting the relevant literature, we found the amount of OVA used in animal models generally ranges from 10 to 100 μg (Yamaki et al, 2005;Tumes et al, 2007;Liu et al, 2010;Oh et al, 2011), whereas the amount of Al(OH) 3 ranges from 1 and 5 mg. Moreover, there are several forms of Al(OH) 3 used in these experiments including powder, gel, solution, and other dosage forms (Yamaki et al, 2005;Zhao et al, 2005;Su et al, 2006;Tumes et al, 2007;Mo et al, 2011). Our study focused on these three dosage forms (powder, gel, and solution) in the production of an AR animal model.…”
Section: Discussionmentioning
confidence: 99%